Development of The Conception of Mechanical Energy Conservation with Interactive Lecture Demonstration Method using Simple Experiments for Grade 7 Students - Willi Anindita Wijanarka; Julius Zai; Winda Noor Santi; Laifa Rahmawati; Mohd Rustam Bin Mohd Rameli (Universitas Ahmad Dahlan, 2022)
The purpose of this research is to develop a student's conception of mechanical energy conservation with the Interactive Lecture Demonstration method. The participants consisted of 19 students of class 7E SMP Muhammadiyah 1 Mlati in 2018/2019 academic year. The analysis of the student's sheet prediction showed that most students do not understand the conception of mechanical energy conservation. After learning applied, it is known that all students have understood the influence of the height of the object on potential energy, 18 of them have understood the influence of the mass of the object on potential energy. While students' understanding of changes in mechanical energy when objects fall and the influence of mass on kinetic energy has increased slightly. Through the Wilcoxon signed-rank test, it was concluded that there was an effect of the use of interactive demonstration methods on student learning outcomes in the matter of mechanical energy conservation conceptions.